On the Chebyshev Polynomial for a Certain Class of Analytic Univalent Functions. (2nd November 2021) - Najafzadeh, Shahram; Acu, Mugur
Abstract : In this work, by considering the Chebyshev polynomial of the first and second kind, a new subclass of univalent functions is defined. We obtain the coefficient estimate, extreme points, and convolution preserving property. Also, we discuss the radii of starlikeness, convexity, and close-to-convexity.